THE ROLE OF FISHERMEN IN IMPROVING THE FAMILY ECONOMY IN SUKA MAJU VILLAGE, TANJUNG TIRAM DISTRICT, BATU BARA REGENCY, NORTH SUMATERA PROVINCE - Nurmaidah; Zuriani; Eva Wardah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
North Sumatra Province. The purpose of this study is what roles fisherwomen do in improving the family economy and calculate how much the income contribution of women fishermen is in helping to improve the family economy. The data analysis used in this research is descriptive qualitative and descriptive quantitative. The types of data used are primary data. The results showed that fisherwomen carried out activities in the field of fisheries such as: splitting salted fish, drying salted fish, splitting anchovies, looking for shells, choosing boiled fish and peeling shrimp shells, in addition to fishery women fishermen also carried out other activities such as: selling cakes, labor washing/ironing and selling herbs. The income contribution given by women fishermen is 40.15% and it means that the income contribution given by women fishermen is in the moderate category and the economic level of the families of women fishermen are in the lower economic level group, however, before the contribution of women fishermen, the average family income is Rp. 1,454,939/month and after the contribution of women fishermen to the family economic level as much as 12.05 % is in the middle level and 87.95 % is in the lower level with an average family income of Rp. 3,410,566/month.